The Generating Function of a Bi-Periodic Leonardo Sequence - da Fonseca, Carlos M. (Armenian Journal of Mathematics, 2024)
In ``"A note on bi-periodic Leonardo sequence", the generating function for a certain bi-periodic Leonardo sequence is claimed.  In this note, we show that the result is not correct. Based on the literature, we establish the correct identity. Possible periodic extensions for the Leonardo sequence are discussed, opening new avenues for results in the area.